Malay National Narrative and Malaysian Historiography: before postmodernity and its discontents, and after too - Clive , S. Kessler (Universiti Kebangsaan Malaysia, 2010)
The publication together in one volume of William R. Roff’s collected essays on Studies on Islam and Society in Southeast Asia, which originally appeared separately between 1964 and 2007, has a double significance. It marks a personal milestone, the completion of fifty years of continuing work on Malay and Islamic social history since his arrival in Kampung Jawa, Klang in 1959. It is also a major event in Malaysian Studies and hence an opportunity to take stock of the field’s, as well as simply Roff’s, achievements. Since his magisterial study of The Origins of Malay Nationalism (1967) Roff has been a towering intellectual presence. His eminent stature and the continuing relevance of his work are confirmed in these fifteen detailed, closely focused and intimately interconnected essays. Roff’s work provides a well-shaped yet broadly inclusive framework that his postmodernist-inspired successors in Malay and Malayan history have sought to question and even displace but which they have never overturned or equalled.